ID4 Is Required for Normal Ependymal Cell Development - Rocamonde, Brenda; Herranz-Pérez, Vicente; Garcia-Verdugo, Jose Manuel; Huillard, Emmanuelle (Frontiers in Neuroscience, 2021)
Ependymal cells are radial glia-derived multiciliated cells lining the lateral ventricles of the brain and spinal cord. Correct development and coordinated cilia beating is essential for proper cerebrospinal fluid flow (CSF) and neurogenesis modulation. Dysfunctions of ependymal cells were associated with transcription factor deregulation. Here we provide evidence that the transcriptional regulator ID4 is involved in ependymal cell development and maturation. We observed that Id4-deficient mice display altered ventricular cell cytoarchitecture, decreased ependymal cell number and enlarged ventricles. In addition, absence of ID4 during embryonic development resulted in decreased ependymal cell number and delayed maturation. Our findings open the way for a potential role of ID4 in ependymal cell development and motor cilia function.